A flame retardant reinforced nylon 6 composition and its preparation method and application

By adding glass fibers, composite flame retardant and titanate coupling agent to nylon 6, a carbon layer "barrier" is formed to block the combustion medium, and the problem of combustion cycle of nylon material during heat melting and decomposition is solved, and a high-strength, high flame retardant and environmentally friendly flame retardant reinforced nylon 6 composition is achieved.

CN118791869BActive Publication Date: 2025-04-25ZHONGSHAN SCHLEMMER AUTOMOTIVE PARTS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411036510.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-04-25
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

Existing nylon materials containing glass fibers tend to cause combustion cycles when melted and decomposed by heat, limiting their application in the field of flame retardant.

Method used

Compositions of nylon 6, glass fibers, composite flame retardant (a mixture of nano zirconium phosphate and cyclic phosphonate) and titanate coupling agent (neoalkoxytris(dioctylpyrophosphate)titanate) are used to block the transmission of combustible gases, oxygen and heat by forming a large number of carbon layers to prevent the glass fiber from exerting the "wick effect".

Benefits of technology

The flame retardant ability and mechanical properties of the glass fiber reinforced nylon composition are significantly improved, reaching the flame retardant properties of UL94 V-0 level, and passing the glow wire test at 960°C.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a flame retardant reinforced nylon 6 composition and a preparation method and application thereof, and relates to the technical field of polymer materials. The invention provides a flame retardant reinforced nylon 6 composition, comprising the following components in parts by weight: 1000 parts of nylon 6, 100-600 parts of glass fiber, 70-150 parts of compounded flame retardant, 3-10 parts of titanate coupling agent, 2-10 parts of antioxidant, and 2-15 parts of lubricant; the compounded flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate, and the weight ratio of the nano zirconium phosphate and the cyclic phosphonate is 1: (1-2); the titanate coupling agent is neoalkoxy tris (dioctyl pyrophosphate acyloxy) titanate. The present invention prepares a flame retardant reinforced nylon 6 composition with high strength, high flame retardancy and environmental protection through the combined use of nylon 6, glass fiber, compounded flame retardant and titanate coupling agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a flame retardant reinforced nylon 6 composition and a preparation method and application thereof. Background Art

[0002] Nylon, English name Polyamide (PA for short), density 1.15g / cm 3 , is a general term for thermoplastic resins containing repeated amide groups [NHCO] on the main chain of the molecule. As a structural material, nylon has high requirements for its mechanical properties and flame retardancy. Adding glass fiber to nylon can significantly improve its mechanical properties, heat resistance, dimensional stability, and aging resistance. With the increasing safety requirements for peripheral products, the goal of raising the flame retardancy of flame-retardant nylon to V0 level is becoming more and more urgent.

[0003] However, when the surface of nylon material containing glass fiber is heated and melted and decomposed, the glass fiber is like a conduit. The melted and decomposed nylon moves along the glass fiber toward the fire source or high temperature field, and the molten part is then decomposed into the combustibles required for combustion. After combustion, the straw effect of glass fiber is more obvious. The heat provided by the combustion causes the polymer to decompose and produce fuel. The fuel maintains combustion and forms a cycle. This is what the industry often calls the "wick effect." If there is no glass fiber to act as a "wick", it is much more difficult for the polymer to burn on the entire surface. Therefore, nylon material containing glass fiber is more flammable than pure nylon, has a high heat generation, and produces flame dripping when burning, causing combustion in a larger range, which greatly limits its application in the flame retardant field. Summary of the invention

[0004] Based on this, the purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a high-strength, high-flame-retardant, environmentally friendly flame-retardant reinforced nylon 6 composition and its preparation method and application.

[0005] To achieve the above object, the technical scheme adopted by the present invention is: a flame retardant reinforced nylon 6 composition, comprising the following components in parts by weight: 1000 parts of nylon 6, 100-600 parts of glass fiber, 70-150 parts of compound flame retardant, 3-10 parts of titanate coupling agent, 2-10 parts of antioxidant, and 2-15 parts of lubricant; the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate, and the weight ratio of the nano zirconium phosphate to the cyclic phosphonate is 1: (1-2); the titanate coupling agent is neoalkoxy tris (dioctyl pyrophosphate acyloxy) titanate.

[0006] The present invention prepares a flame-retardant reinforced nylon 6 composition with high strength, high flame retardancy and environmental protection through the combined use of nylon 6, glass fiber, compound flame retardant and titanate coupling agent. The present invention uses a special coupling agent, neoalkoxy tris (dioctyl pyrophosphate acyloxy) titanate, which has three functional groups with organic reaction activity in its molecular structure, including dioctyl pyrophosphate acyloxy and a neoalkoxy group with an ether structure. It can not only better disperse the flame retardant in the nylon composition, but also greatly increase the interfacial bonding force between the glass fiber, the flame retardant and the nylon matrix. Further improve the flame retardant properties and mechanical properties. The present invention uses a compound flame retardant of nano zirconium phosphate and cyclic phosphonate, and the two work synergistically to form a large number of carbon layer "barriers" to block the transmission of combustible gases, oxygen and heat, so that the glass fiber cannot play a "wick effect", which greatly improves the flame retardant ability of the glass fiber reinforced nylon composition. In the present invention, the nano zirconium phosphate is a flaky nano material, and the interlayer contains a large amount of Acid point and Lewis acid point. Zirconium phosphate is used in combination with cyclic phosphonates. When the nylon composition burns, the cyclic phosphonates release phosphonate decomposition products during the combustion process. The products can form a gel layer in the combustion area. Nano zirconium phosphate can quickly catalyze the cross-linking of nylon into carbon. The two work together to form a large number of carbon layer "barriers" to block the transmission of combustible gases, oxygen and heat, so that the glass fiber cannot play a "wick effect", which greatly improves the flame retardant ability of the glass fiber reinforced nylon composition.

[0007] Preferably, the average particle size D50 of the nano zirconium phosphate is 100-2000 nm.

[0008] Preferably, the nylon 6 has a melt index of 10-120 g / 10 min under the conditions of a test temperature of 235° C. and a load of 2.16 kg according to ASTM D1238-2010; the glass fiber is an alkali-free glass fiber, and the monofilament diameter of the alkali-free glass fiber is 10-25 μm.

[0009] Preferably, the antioxidant is at least one of hindered amines, hindered phenols, thiols, and phosphites, and the lubricant is at least one of white oil, natural paraffin, oleamide, ethylene bisstearamide, stearic acid, butyl stearate, and microcrystalline paraffin.

[0010] More preferably, the antioxidant is at least one of antioxidant 1098, antioxidant 1076, antioxidant 1010, antioxidant 300, and antioxidant 168. In one embodiment, the antioxidant is a mixture of antioxidant 1098 and antioxidant 168 in a mass ratio of 1:1.

[0011] In addition, the present invention provides a method for preparing the flame retardant reinforced nylon 6 composition, comprising the following steps:

[0012] (1) Weigh various raw materials according to the ratio;

[0013] (2) placing the above raw materials in a twin-screw extruder, and granulating them after melt extrusion to obtain the flame retardant reinforced nylon 6 composition, wherein the glass fiber is added by side feeding.

[0014] Preferably, the temperature of zone 1 of the twin-screw extruder is 140-180°C, the temperature of zone 2 is 180-210°C, the temperature of zone 3 is 220-230°C, the temperature of zone 4 is 230-240°C, the temperature of zone 5 is 230-245°C, the temperature of zone 6 is 230-250°C, and the temperature of the die head is 230-255°C.

[0015] Furthermore, the present invention provides the use of the flame retardant reinforced nylon 6 composition in peripheral parts of new energy vehicles. Preferably, the peripheral parts of new energy vehicles include one of a water chamber, a fan, a battery pack, and a battery grid.

[0016] Compared with the prior art, the beneficial effects of the present invention are:

[0017] The present invention prepares a flame-retardant reinforced nylon 6 composition with high strength, high flame retardancy and environmental protection by using nylon 6, glass fiber, compound flame retardant and titanate coupling agent in combination. The present invention uses a special coupling agent, neoalkoxy tris (dioctyl pyrophosphate acyloxy) titanate, which has three functional groups with organic reaction activity in its molecular structure, including dioctyl pyrophosphate acyloxy and a neoalkoxy group with an ether structure, which can not only make the flame retardant uniformly dispersed in the nylon composition, but also can greatly increase the interface bonding force between the glass fiber, the flame retardant and the nylon matrix, further improving the flame retardant performance and mechanical properties.

[0018] The present invention uses a composite flame retardant of nano zirconium phosphate and cyclic phosphonate, which work together to form a large number of carbon layers "barriers" to block the transmission of combustible gas, oxygen and heat, so that the glass fiber cannot play a "wick effect", greatly improving the flame retardant ability of the glass fiber reinforced nylon composition. The nano zirconium phosphate in the present invention is a sheet-like nano material, and the interlayer contains a large amount of Acid point and Lewis acid point. Zirconium phosphate is used in combination with cyclic phosphonates. When the nylon composition burns, the cyclic phosphonates release phosphonate decomposition products during the combustion process. The products can form a gel layer in the combustion area. Nano zirconium phosphate can quickly catalyze the cross-linking of nylon into carbon. The two work together to form a large number of carbon layer "barriers" to block the transmission of combustible gases, oxygen and heat, so that the glass fiber cannot play a "wick effect", which greatly improves the flame retardant ability of the glass fiber reinforced nylon composition. DETAILED DESCRIPTION

[0019] Unless otherwise specified, the various raw materials of the present invention can be obtained commercially; or prepared according to conventional methods in the art. Unless otherwise defined or specified, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the method of the present invention. Other aspects of the present invention are obvious to those skilled in the art due to the disclosure herein. The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0020] The experimental methods in the following examples without specifying specific conditions are usually measured according to national standards. If there is no corresponding national standard, it is carried out according to the general international standards, conventional conditions, or according to the conditions recommended by the manufacturer. Unless otherwise specified, all parts are by weight and all percentages are by weight.

[0021] It should be noted that, for those skilled in the art, several changes and improvements can be made without departing from the concept of the present invention, which all fall within the protection scope of the present invention.

[0022] In the following examples and comparative examples, some raw material specifications and sources are, but not limited to, these materials:

[0023] Nylon 6-1: Brand B3S, melt index 35g / 10min (235℃, 2.16kg), from BASF, Germany.

[0024] Nylon 6-2: brand TP-4208, melt index 102.1g / 10min (235℃, 2.16kg), Jisheng Company.

[0025] Glass fiber-1: grade 266, monofilament diameter 13 μm, Jushi Group.

[0026] Glass fiber-2: brand 386T, monofilament diameter 24μm, Jushi Group.

[0027] The supplier of nano zirconium phosphate is Wuhan Linsheng Technology Co., Ltd., and the average particle sizes are 100nm, 500nm, 1000nm, and 2000nm respectively.

[0028] Cyclic phosphonates: The supplier is Guangzhou Shanghe Chemical Technology Co., Ltd.

[0029] Titanate coupling agent-neoalkoxy tri(dioctyl pyrophosphate) titanate, silane coupling agent-KH550, titanate coupling agent-isopropoxy tristearyl titanate, all suppliers are Nanjing Nengde New Materials.

[0030] Antioxidant: A mixture of antioxidant 1098 and antioxidant 168 in a mass ratio of 1:1, supplied by DuPont of the United States.

[0031] Lubricant: ethylene bisstearamide, butyl stearate, both suppliers are Jining Sanshi Biotechnology Co., Ltd.

[0032] In the following embodiments and comparative examples, the testing methods and standards of various performance parameters are as follows:

[0033] Mechanical properties: Tensile strength was tested according to ISO 527-2-2012.

[0034] Flame retardant performance: refer to standard UL94-2011, vertical burning 1.6mm thickness, sample size is 125mm×13mm×5mm;

[0035] Glow wire temperature (GWIT): refer to standard GB-T 5169.10-2017.

[0036] Examples 1-12 and Comparative Examples 1-8

[0037] Example 1

[0038] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0039] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0040] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0041] Example 2

[0042] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0043] Pour 1000 parts of nylon 6-1, 80 parts of compound flame retardant, 4 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 2 parts of antioxidant and 2 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 120 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0044] The temperature of zone 1 of the twin-screw extruder is 140°C, the temperature of zone 2 is 180°C, the temperature of zone 3 is 220°C, the temperature of zone 4 is 230°C, the temperature of zone 5 is 230°C, the temperature of zone 6 is 240°C, and the temperature of the die head is 240°C.

[0045] Example 3

[0046] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0047] Pour 1000 parts of nylon 6-1, 140 parts of compound flame retardant, 10 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 10 parts of antioxidant and 14 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 560 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0048] The temperature of zone 1 of the twin-screw extruder is 180°C, the temperature of zone 2 is 210°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0049] Example 4

[0050] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0051] Pour 1000 parts of nylon 6-1, 100 parts of compound flame retardant, 5 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 4 parts of antioxidant and 5 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 240 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0052] The temperature of zone 1 of the twin-screw extruder is 155°C, the temperature of zone 2 is 190°C, the temperature of zone 3 is 225°C, the temperature of zone 4 is 235°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 250°C.

[0053] Example 5

[0054] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0055] Pour 1000 parts of nylon 6-1, 100 parts of compound flame retardant, 5 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 4 parts of antioxidant and 5 parts of lubricant butyl stearate into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 320 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0056] The temperature of zone 1 of the twin-screw extruder is 155°C, the temperature of zone 2 is 190°C, the temperature of zone 3 is 225°C, the temperature of zone 4 is 235°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 250°C.

[0057] Example 6

[0058] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0059] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0060] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0061] Example 7

[0062] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:2, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0063] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0064] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0065] Example 8

[0066] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0067] Pour 1000 parts of nylon 6-2, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0068] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0069] Example 9

[0070] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0071] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-2 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0072] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0073] Example 10

[0074] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 100 nm.

[0075] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0076] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0077] Embodiment 11

[0078] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 1000 nm.

[0079] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0080] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0081] Example 12

[0082] In this embodiment, the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 2000 nm.

[0083] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0084] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0085] Each comparative example of the present invention is compared with Example 1, which is as follows

[0086] Comparative Example 1

[0087] The compound flame retardant in this comparative example is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0088] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of silane coupling agent KH550, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0089] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0090] Comparative Example 2

[0091] The compound flame retardant in this comparative example is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0092] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of isopropoxy tristearate acyloxy titanate (titanium ester coupling agent), 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0093] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0094] Comparative Example 3

[0095] The average particle size of the nano zirconium phosphate in this comparative example is 500 nm.

[0096] 1000 parts of nylon 6-1, 120 parts of nano zirconium phosphate, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide are poured into a high-speed mixer, mixed evenly and added into a twin-screw extruder, and 450 parts of glass fiber-1 are added from the glass fiber feeding port at the same time. The composition is granulated after melt extrusion.

[0097] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0098] Comparative Example 4

[0099] Pour 1000 parts of nylon 6-1, 120 parts of cyclic phosphonate, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0100] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0101] Comparative Example 5

[0102] The compound flame retardant in this comparative example is a mixture of nano magnesium hydroxide and cyclic phosphonate in a ratio of 1:1.5, wherein the average particle size of the nano magnesium hydroxide is 500 nm.

[0103] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0104] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0105] Comparative Example 6

[0106] The compound flame retardant in this comparative example is a mixture of nano zirconium phosphate and triphenyl phosphate in a ratio of 1:1.5, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0107] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0108] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0109] Comparative Example 7

[0110] The compound flame retardant in this comparative example is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 1:4, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0111] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0112] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0113] Comparative Example 8

[0114] The compound flame retardant in this comparative example is a mixture of nano zirconium phosphate and cyclic phosphonate in a ratio of 2:1, wherein the average particle size of the nano zirconium phosphate is 500 nm.

[0115] Pour 1000 parts of nylon 6-1, 120 parts of compound flame retardant, 8 parts of neoalkoxy tri(dioctyl pyrophosphate) titanate, 8 parts of antioxidant and 12 parts of lubricant ethylene bisstearamide into a high-speed mixer, mix well and add into a twin-screw extruder, and at the same time add 450 parts of glass fiber-1 from the glass fiber feeding port, and the composition is granulated after melt extrusion.

[0116] The temperature of zone 1 of the twin-screw extruder is 160°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 245°C, the temperature of zone 6 is 250°C, and the temperature of the die head is 255°C.

[0117] Please see Table 1 for data of various embodiments and comparative examples.

[0118] Table 1 Performance data

[0119] Tensile strength MPa UL94 (thickness 1.6mm) Glow wire (S, 960℃) Example 1 183 V0 qualified Example 2 119 V0 qualified Example 3 195 V0 qualified Example 4 161 V0 qualified Example 5 169 V0 qualified Example 6 182 V0 qualified Example 7 175 V0 qualified Example 8 169 V0 qualified Example 9 171 V0 qualified Example 10 177 V0 qualified Embodiment 11 170 V0 qualified Example 12 166 V0 qualified Comparative Example 1 133 V1 Failure Comparative Example 2 147 V1 qualified Comparative Example 3 179 V2 Failure Comparative Example 4 164 V1 Failure Comparative Example 5 172 V1 Failure Comparative Example 6 181 V1 Failure Comparative Example 7 178 V1 Failure Comparative Example 8 183 V1 Failure

[0120] As can be seen from Table 1 above, the flame retardant reinforced nylon 6 composition prepared by the present invention can achieve UL94 V-0 level of flame retardancy, can pass the 960°C glow wire test, and the tensile strength performance of the material is relatively excellent.

[0121] It can be seen from Example 1 and Comparative Examples 1-2 that the coupling agent neoalkoxy tri(dioctyl pyrophosphate) titanate of the present application can not only better improve the dispersibility of glass fiber and nano zirconium phosphate in the composition, but also greatly increase the interfacial bonding strength between glass fiber, nano zirconium phosphate and nylon matrix, compared with the common coupling agent KH550 and isopropoxy tristearate titanate.

[0122] It can be seen from Example 1 and Comparative Example 3 that single nano zirconium phosphate does not significantly improve the flame retardant properties of the composition, the UL94 test result is only V2, and the 960°C glow-wire test cannot be passed; when the nano zirconium phosphate content is too high, its strength also decreases.

[0123] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily.

Claims

1. A flame retardant reinforced nylon 6 composition, characterized in that: The invention comprises the following components in parts by weight: 1000 parts of nylon 6, 100-600 parts of glass fiber, 70-150 parts of compound flame retardant, 3-10 parts of titanate coupling agent, 2-10 parts of antioxidant and 2-15 parts of lubricant; the compound flame retardant is a mixture of nano zirconium phosphate and cyclic phosphonate, and the weight ratio of the nano zirconium phosphate to the cyclic phosphonate is 1:(1-2); the titanate coupling agent is neoalkoxy tris (dioctyl pyrophosphate acyloxy) titanate; the average particle size D50 of the nano zirconium phosphate is 100-2000nm.

2. The flame retardant reinforced nylon 6 composition according to claim 1, characterized in that: The melting index of the nylon 6 is 10-120 g / 10 min under the conditions of a test temperature of 235° C. and a load of 2.16 kg according to ASTM D1238-2010; the glass fiber is an alkali-free glass fiber, and the monofilament diameter of the alkali-free glass fiber is 10-25 μm.

3. The flame retardant reinforced nylon 6 composition according to claim 1, characterized in that: The antioxidant is at least one of hindered amines, hindered phenols, thiols, and phosphites; the lubricant is at least one of white oil, oleamide, ethylene bisstearamide, stearic acid, and butyl stearate.

4. The flame retardant reinforced nylon 6 composition according to claim 1, characterized in that: The lubricant is natural paraffin.

5. The flame retardant reinforced nylon 6 composition according to claim 1, characterized in that: The lubricant is microcrystalline wax.

6. A method for preparing the flame retardant reinforced nylon 6 composition according to any one of claims 1 to 5, characterized in that: The steps include: (1) Weigh various raw materials according to the ratio; (2) The raw materials are placed in a twin-screw extruder, melt-extruded and pelletized to obtain the flame-retardant reinforced nylon 6 composition, wherein the glass fiber is added by side feeding.

7. The method for preparing the flame retardant reinforced nylon 6 composition according to claim 6, characterized in that: The temperature of the twin-screw extruder zone 1 is 140-180°C, the temperature of zone 2 is 180-210°C, the temperature of zone 3 is 220-230°C, the temperature of zone 4 is 230-240°C, the temperature of zone 5 is 230-245°C, the temperature of zone 6 is 230-250°C, and the temperature of the die head is 230-255°C.

8. Use of the flame retardant reinforced nylon 6 composition according to any one of claims 1 to 5 in peripheral parts of new energy vehicles.

9. A use as claimed in claim 8, characterized in that The peripheral parts of the new energy vehicle include one of a water chamber, a fan, a battery pack, and a battery grille.

Citation Information

Patent Citations

  • PA / AS-base (polyamide / acrylonitrile-styrene-base) resin composite and preparation method thereof

    CN106380839A

  • Enhanced flame-retardant nylon composition with high glow wire initiation temperature and preparation method thereof

    CN109401303A